Industrial Sector output and Its Relationship with Government Expenditure, Credit, and Foreign Aid in Nepal - Dahal, Arjun Kumar; Khatiwada, Bijayahari (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
The study's goal is to look into the state, long-run relationship, and casual link of government spending, commercial bank lending, and foreign aid to Nepal's industrial sector output. The research design for this study is descriptive and analytical. The secondary data are processed using Excel and EViews10 software from 1989/90 to 2018/19. The Johnsen Co-integration test and Granger Causality test describe and analyze the relation and causal impact of variables. The credit of commercial banks highly influences industrial output. The industrial sector output, government expenditure, loans, and foreign aid were Co-integrated or had long-run association ship. This paper contributes to the policy debate on whether government expenditure and foreign support to the industrial sector are justified or not. The author is unaware of another study, finding, and location related to industrial output and its affecting factors like government expenditure, loans, and foreign aid.